2017
DOI: 10.1037/emo0000224
|View full text |Cite
|
Sign up to set email alerts
|

Sad man’s nose: Emotion induction and olfactory perception.

Abstract: Emotional and olfactory processing is frequently shown to be closely linked both anatomically and functionally. Depression, a disease closely related to the emotional state of sadness, has been shown to be associated with a decrease in olfactory sensitivity. The present study focuses on the state of sadness in n = 31 healthy subjects in order to investigate the specific contribution of this affective state in the modulation of olfactory processing. A sad or indifferent affective state was induced using 2 movie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…We did not investigate the relation between valence and arousal at the ideographic (within-person) level, which is known to depend on individual characteristics such as mood [68], physiological state [69], gender [70], age [71], and cultural background [72][73][74].…”
Section: Limitationsmentioning
confidence: 99%
“…We did not investigate the relation between valence and arousal at the ideographic (within-person) level, which is known to depend on individual characteristics such as mood [68], physiological state [69], gender [70], age [71], and cultural background [72][73][74].…”
Section: Limitationsmentioning
confidence: 99%
“…Hoover also points to the complex link between perception of odours and satiation, noting that with reduced olfactory function, food choices may shift to high fat, salt and sugary foods that stimulate 'taste' but not flavour. Moreover, research is now showing that the size of the olfactory bulb appears to have distinct correlates with the experience of depression (Flohr et al, 2017;Croy et al, 2014). The physical 'stuff' of food when savouring the smell of it or eating, stimulate the physical 'stuff' of the body through which emotions and feelings manifest, but not equally.…”
Section: The Sensory Turn and Visceral Geographymentioning
confidence: 99%
“…Comorbidities may also modify perception of food modalities. The higher prevalence of depression in the ageing population could justify the differential response towards olfactory cues as compared to the young [ 47 ]. Diabetes mellitus type 2 (DM2) may also work as an independent risk factor for olfactory and cognitive dysfunction, whereas early studies showed a preference for sweet foods, especially in AD and VD [ 48 ].…”
Section: Is Food Still Perceived As Alluring and Delicious With Agmentioning
confidence: 99%